Contact Analysis of Heavy Load Ball Screw Assembly of Continuous Casting Tundish Car - Shi Jialian; Liu Jinghui; Wu Jin; Zhao Xu (Jixie chuandong)
In order to guarantee the structural safety and reliability as well as sufficient strength and stiffness of heavy load ball screw assembly of tundish car,the contact statics analysis of the ball screw assembly is conducted by the finite element software ANSYS,and the impact of contact angle and load on the stress and deformation of ball screw assembly is explored. The results show that the maximum stress of the ball screw assembly is 1093. 7 MPa,which is smaller than the allowable stress of the structure and therefore satisfies the requirements of stiffness and strength. Moreover,the contact stress and deformation of the ball screw assembly decreases with the increasing of the contact angle and increases with the increasing of the load.